Kohn-Luttinger effect and anomalous pairing in repulsive Fermi-systems at low density (Review Article) - Kagan, M.Yu.; Efremov, D.V.; Mar’enko, M.S.; Val’kov, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
In the large variety of models such as 3D and 2D Fermi-gas model with hard-core repulsion, 3D and 2D Hubbard model, and Shubin–Vonsovsky model we demonstrate the possibility of triplet p-wave pairing at low electron density. We show that the critical temperature of the p-wave pairing can be strongly increased in a spinpolarizedcase or in a two-band situation already at low density and reach experimentally observable values of (1–5) K. We also discuss briefly d-wave pairing and high-Tc superconductivity with Tc ~ 100 K which arises in the extended Hubbard model and in the generalized t-J model close to half-filling.